Desenvolvimento de um índice para a avaliação da ciclabilidade na cidade de Aracaju - Andrade, José Waldson Costa de (2018)
The challenges of urban mobility demand a new way of thinking and of managing the displacement of goods and people in Brazilian cities. Bicycles as a means of transportation become then an important tool for urban sustainability and allow for a good rapport between citizens and the urban space. This research aims to come up with a Cyclability Index through the use of Socio-environmental Indicators. Cyclability sets out to elaborate on tools that analyze the acceptance of bicycles in cities as an efficient means of transportation and how much they should considered positive by society as a whole and the public administration. Thus, the main goal of this research was to come up with a cyclability index in the city of Aracaju focusing on use of bicycles as a means of transportation; alongside, the specific goals seek to identify the weaknesses and the potential of bicycle motivated urban mobility; analyze, through socio-environmental indicators, the technical, institutional, environmental, structural, political and cultural conditions of bicycle use and present possible policies to enhance these conditions. The adopted methodology chooses five categories composed of 13 indicators, that through data collection in four different research zones, presents results which match this essay`s goals. The Cyclability Index of Aracaju, it was found, scored 1.13, which means it is on critical level and that bicycle use conditions are poor in the city. For this reason, short-term responses are needed to address the issue. This research drew the conclusion that the public administration should as soon as possible propose intervention measures and governance policies to plan and overhaul the city`s cycle lanes regarding their environmental, infrastructural and security aspects.